Faktor Pendapatan dan Pendidikan Sebagai Pencetus Migrasi di Kabupaten Jeneponto Sulawesi Selatan serta Dampaknya terhadap Perekonomian - Syawaluddin S; Mei K. Abdullah (Al-Buhuts, 2022)
This study will reveal the Determinant Factors of Outgoing Migration of the People of Jeneponto Regency, South Sulawesi Province, the problem of this research is the phenomenon of the Jeneponto people who migrate out especially during the dry season, who migrate to several destination areas such as Makassar City, Palopo City and the City of Mamaju. This type of research is quantitative, where data processing is based on a model built using multiple linear regression statistical analysis tools, taking income level (X1), education level (X2), as the independent variable and Migration Y) as the dependent variable. by first doing some statistical tests. The population in this study amounted to 5,317 respondents who were at fault from the area where the population was the most migrating. while the number of samples as many as 89 respondents, namely residents who migrated out of Jeneponto Regency. The results of the study using statistical tests showed that the level of income (X1) and the labor force (X2) had a positive effect on the occurrence of migration, and from the regression results that had been carried out the R-Squae (R2) value of 0.766 it could be concluded that the large percentage of the migration variable could be explained by three independent variables, namely income per capita, level of education and labor. strength of 76.4% (0.764) while the rest with a value of 23.6% (0.236) which is explained by other variables not included in this study. In Jeneponto, migration is dominated by the productive age population between 15-25 years, which is 67% and is the largest group of people who migrate. If population growth is accompanied by established skills of the workforce, it will certainly increase productivity, so that it will move all factors of production, it will increase the aggregate supply and high demand, which will ultimately improve the macroeconomic performance of a region.